Kubera accompanied by his mount the elephant - Temples of India Project Team (Jio Institute, 2024)
Kubera, accompanied by his mount, the elephant, is depicted with four arms. In his upper arms, he holds a symbol of wealth and abundance —a money bag. Though his lower arms are damaged, it is evident that he once wielded a gada (mace) in his lower right hand and a kamandalu (water pot) in his lower left hand.